2022
DOI: 10.1007/s11031-022-09931-8
|View full text |Cite
|
Sign up to set email alerts
|

Disgustingly perfect: An examination of disgust, perfectionism, and gender

Abstract: High levels of disgust and perfectionism co-exist in some clinical disorders raising questions about the relationship between the two. This research evaluated socially-related and physically-related disgust in people with varying levels of perfectionism. In Study 1, 120 college students participated in a state emotion-eliciting scenario task, then completed both the Almost Perfect Scale-Revised and the Three Dimensions of Disgust Survey (TDDS). In Study 2, 380 Qualtrics users completed the scenarios, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…This re ects that the effect of perfectionism on sleep quality is not affected by gender or academic year. However, it was reported that females tend to have greater means across the two scales (FMPS and PSQI) than males, Which is in line with a previous study conducted in the USA that revealed that women were more likely than men to be perfectionists (72% of women versus 65% of men) (27).…”
Section: Discussionsupporting
confidence: 85%
“…This re ects that the effect of perfectionism on sleep quality is not affected by gender or academic year. However, it was reported that females tend to have greater means across the two scales (FMPS and PSQI) than males, Which is in line with a previous study conducted in the USA that revealed that women were more likely than men to be perfectionists (72% of women versus 65% of men) (27).…”
Section: Discussionsupporting
confidence: 85%